KINERJA PT PLN UNIT INDUK DISTRIBUSI JAKARTA RAYA DENGAN SUPPLY CHAIN OPERATION REFERENCE - Arga Santoso; Alfi Nurzaki; Chano Benawan; Didin Wahyudin; Sugeng Santoso (Distribusi - Journal of Management and Business, 2020)
PT PLN (Persero) Jakarta Raya Main Distribution Unit continuously improves services to customers by conducting new installations following the targeted time. Installation speed is one of the factors that influence the function and customer perception of the company. PT PLN (Persero) Jakarta Raya Distribution Main Unit serves the connection of Low Voltage (TR) and Medium Voltage (TM) electricity. Based on the identification carried out, it was found that there were obstacles experienced by the company, causing the connection work to belong. This is located in the Medium Voltage service pattern of 100 days required above the 100-day target. The length of the service process is experiencing problems from the external and internal sides of the company. Therefore, there needs to be an in-depth analysis of certain methods to achieve the targets set the following year. This study examines the attributes of reliability and responsiveness using the Perfect Order Fulfillment (POF) and Order Fulfilment Cycle Time (OFCT) metrics. The results showed that the licensing factor and customer unpreparedness were the main reasons for the delay in installing the 100-day Medium Voltage electricity pattern.